Towards a sustainable NGO intervention on child protection: taking indigenous knowledge seriously. Issue 2 (17th February 2021) - Yeboah, Sampson A.; Daniel, Marguerite
ABSTRACT: The development and well-being of children are important to governments. In Ghana and elsewhere in Africa, policies directing children's welfare are mostly influenced by the United Nations Convention on the Rights of the Child (UNCRC). Despite enormous energy devoted to generating policies and guidelines, little attention is given to the rejection of indigenous knowledge on childhood, and its effect on the sustainable implementation of child-focused interventions. This article uses an ethnographic approach to explore rural parents' attitudes to an NGO intervention on children's rights to basic schooling, and the illegality of child labour. Based on the study findings, the article discusses lessons for practice.